Relationship of sleep quality and sleepiness state with antisaccade performance in healthy young individuals having no sleep deprivation. - Yilmaz, Alpaslan (Progress in Nutrition, 2021)
Study Objectives: It is a fact that sleep affects the function of many brain regions. Clinical and / or experimental sleep and sleep deprivation studies are not easy to implement, as they require both participants and researchers to spend long periods in the laboratory or clinic. Often, the clinician or researcher uses subjective methods to obtain information about the quality of sleep that patients or participants have. For this purpose, the Pittsburgh Sleep Quality Index (PSQI) and the Epworth Sleepiness Scale (ESS) are frequently used. In this study, it is aimed to present concrete neurobiological evidence by testing whether there is a correlation between the data obtained with these subjective methods, which are frequently used in the clinic and the saccadic eye movements of healthy and young individuals. Methods:  Eye movements were recorded by using the electrooculographic method and PSQI and ESS scores were determined by questionnaire method from 48 healthy (31 male and 17 female) individuals between 18-25 years of age. Results:  There was a positive correlation between the PSQI scores and antisaccade spatial errors, a negative correlation between ESS scores and maximum saccade velocities, and a positive correlation between ESS scores and the number of antisaccade directional errors. Conclusion:  it may be considered that sleep quality and sleepiness state can effect the saccadic system antisaccade paradigm in young individuals who have not been diagnosed with any psychiatric, neurological, and systemic diseases before and who have not had acute sleep deprivation for at least the past three days.